2018
DOI: 10.3390/cryst8050209
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Elastic, Vibrational and Structural Study of Monazite-Type GdPO4 from Ab Initio Simulations

Abstract: The GdPO 4 monazite-type has been studied under high pressure by first principles calculations in the framework of density functional theory. This study focuses on the structural, dynamical, and elastic properties of this material. Information about the structure and its evolution under pressure, the equation of state, and its compressibility are reported. The evolution of the Raman and Infrared frequencies, as well as their pressure coefficients are also presented. Finally, the study of the elastic constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Whereas the peak positions stay essentially constant over time, within the ±1 cm –1 instrumental uncertainty, the fwhm varies significantly for some peaks. The former observation means that the A g vibrational lines are characterized by a very small (or vanishing) Grueneisen parameter, which is in reasonable agreement with the data reported in Munoz and Rodriguez–Hernandez . Our results differ from those for monazites irradiated by Au ions which showed that the A g band at 970 cm –1 exhibits an increase of the fwhm of approximately 30 cm –1 and a downshift in the peak energy of approximately 20 cm –1 for a radiation damage of the order of 0.04 dpa (corresponding to a fluence of 4 × 10 13 Au ions cm –2 ).…”
Section: Resultssupporting
confidence: 91%
“…Whereas the peak positions stay essentially constant over time, within the ±1 cm –1 instrumental uncertainty, the fwhm varies significantly for some peaks. The former observation means that the A g vibrational lines are characterized by a very small (or vanishing) Grueneisen parameter, which is in reasonable agreement with the data reported in Munoz and Rodriguez–Hernandez . Our results differ from those for monazites irradiated by Au ions which showed that the A g band at 970 cm –1 exhibits an increase of the fwhm of approximately 30 cm –1 and a downshift in the peak energy of approximately 20 cm –1 for a radiation damage of the order of 0.04 dpa (corresponding to a fluence of 4 × 10 13 Au ions cm –2 ).…”
Section: Resultssupporting
confidence: 91%
“…Although increasing with pressure, the Poisson ratio has a value <0.5 across the studied pressure range (Figure S5d), thus reflecting both the slightly anisotropic compressibility of wolframite-type CoWO 4 (see results in the XRD section) and an increasing ionic character of the chemical bond. 59,60 Finally, the bulk/shear ratio also increases under compression, indicating the high ductility of CoWO 4 (Figure S5d).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 93%
“…High-pressure (HP) studies of several A PO 4 orthophosphates have been reported in the literature; i.e., where zircon- and monazite-type phosphates have been broadly studied. The pressure-induced structural sequence has been understood, with several new HP phases discovered and their crystal structures solved. In addition, the influence of pressure in the vibrational properties and unit-cell parameters has been well established.…”
Section: Introductionmentioning
confidence: 99%